Disruption of adult expression of sexually selected traits by developmental exposure to bisphenol A - Jašarević, Eldin (National Academy of Sciences, 2011)
Exposure to endocrine disrupting compounds (EDCs), such as bisphenol A (BPA), may cause adverse health effects in wildlife and humans, but controversy remains as to what traits are most sensitive to EDCs and might serve as barometers of exposure. Expression of sexually selected traits that have evolved through intrasexual competition for mates and intersexual choice of mating partner are more dependent on developmental and physical condition of an animal than naturally selected traits and thus might be particularly vulnerable to disruption by developmental exposure to EDCs. We have used the deer mouse (Peromyscus maniculatus) as a model to test this hypothesis. Adult male–male competition for mates in this species is supported by enhanced spatial navigational and exploratory abilities, which enable males to search for prospective, widely dispersed females. Male deer mice exposed to BPA or ethinyl estradiol (EE) through maternal diet showed no changes in external phenotype, sensory development, or adult circulating concentrations of testosterone and corticosterone, but spatial learning abilities and exploratory behaviors were severely compromised compared with control males. Because these traits are not sexually selected in females, BPA exposure predictably had no effect, although EE-exposed females demonstrated enhanced spatial navigational abilities. Both BPA-exposed and control females preferred control males to BPA-exposed males. Our demonstration that developmental exposure to BPA compromises cognitive abilities and behaviors essential for males to reproduce successfully has broad implications for other species, including our own. Thus, sexually selected traits might provide useful biomarkers to assess risk of environmental contamination in animal and human populations.